Liposomal Delivery of Mycophenolic Acid With Quercetin for Improved Breast Cancer Therapy in SD Rats - Patel, Gopal; Thakur, Neeraj Singh; Kushwah, Varun; Patil, Mahesh D.; Nile, Shivraj Hariram; Jain, Sanyog; Banerjee, Uttam Chand; Kai, Guoyin (Frontiers in Bioengineering and Biotechnology, 2020)
The present study explores the influence of mycophenolic acid (MPA) in combination therapy with quercetin (QC) (impeding MPA metabolic rate) delivered using the liposomal nanoparticles (LNPs). Mycophenolic acid liposome nanoparticles (MPA-LNPs) and quercetin liposome nanoparticles (QC-LNPs) were individually prepared and comprehensively characterized. The size of prepared MPA-LNPs and QC-LNPs were found to be 183 ± 13 and 157 ± 09.8, respectively. The in vitro studies revealed the higher cellular uptake and cytotoxicity of combined therapy (MPA-LNPs + QC-LNPs) compared to individual ones. Moreover pharmacokinetics studies in female SD-rat shown higher T1/2 value (1.94 fold) of combined therapy compared to MPA. Furthermore, in vivo anticancer activity in combination of MPA-LNPs and QC-LNPs was also significantly higher related to other treatments groups. The combination therapy of liposomes revealed the new therapeutic approach for the treatment of breast cancer.